V.2 - "Sitarammaya, P." (Bombay, 1946)
This publication (in 2 volumes) is not only a short history of the Indian National Congress but to a considerable extent the history of the Indian people. These volumes give us a glimpse of how the Congress, over the past years, traversed the path of Indian nation-building through extremely difficult challenges, both external and internal. This glorious history should serve as a guide and an anchor in helping the country negotiate future challenges.
Keywords: Political Parties-India